2012
DOI: 10.1039/c2dt30883e
|View full text |Cite
|
Sign up to set email alerts
|

Novel heterostructured Bi2S3/BiOI photocatalyst: facile preparation, characterization and visible light photocatalytic performance

Abstract: Novel Bi(2)S(3)/BiOI heterostructures were successfully synthesized through a facile and economical ion exchange method between BiOI and thioacetamide (CH(3)CSNH(2)), and characterized by multiform techniques, such as XRD, Raman, FT-IR, XPS, SEM, TEM, HRTEM, SAED, BET and DRS. The obtained Bi(2)S(3)/BiOI photocatalysts showed excellent photocatalytic performance for decomposing organic dye methyl orange (MO) compared with pure BiOI under visible light irradiation (λ > 420 nm). Among the Bi(2)S(3)/BiOI photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
157
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(166 citation statements)
references
References 70 publications
(60 reference statements)
9
157
0
Order By: Relevance
“…It is revealed that in the sample U1.0, U3.0, and U5.0 the Bi 2 S 3 is homogenously dispersed on (BiO) 2 CO 3 as nanoparticles but not a shell, which is different from the case of U7.0. When a shell was formed on the surface of (BiO) 2 CO 3 (U7.0), the transferred electrons from the CB of Bi 2 S 3 to the CB of (BiO) 2 CO 3 would be kept away from the reactants; furthermore, the accumulation of electrons in the CB of (BiO) 2 CO 3 would lead to a built-in potential, preventing the charge separation, thus leading to the photodegradation activity recede [37]. By comparing the shapes of the photoluminescence spectra of U5.0 and N5.0, it is found that they exhibit similar PL spectra but different intensities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is revealed that in the sample U1.0, U3.0, and U5.0 the Bi 2 S 3 is homogenously dispersed on (BiO) 2 CO 3 as nanoparticles but not a shell, which is different from the case of U7.0. When a shell was formed on the surface of (BiO) 2 CO 3 (U7.0), the transferred electrons from the CB of Bi 2 S 3 to the CB of (BiO) 2 CO 3 would be kept away from the reactants; furthermore, the accumulation of electrons in the CB of (BiO) 2 CO 3 would lead to a built-in potential, preventing the charge separation, thus leading to the photodegradation activity recede [37]. By comparing the shapes of the photoluminescence spectra of U5.0 and N5.0, it is found that they exhibit similar PL spectra but different intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the Bi 2 S 3 /(BiO) 2 CO 3 can be synthesized through a facile ion-exchange reaction between (BiO) 2 CO 3 and S 2-ions. Due to the rather low solubility of Bi 2 S 3 in water (K sp = 1.0 9 10 -97 ) [37], the formed Bi 2 S 3 should mainly deposit on the surface of (BiO) 2 CO 3 , and the amount of Bi 2 S 3 should be mainly determined by both the mass transfer of S 2-ions from bulk solution to the surface of (BiO) 2 CO 3 and the concentration of surface Bi 3? ions on (BiO) 2 CO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The two intensive peaks at 1386 and 1466 cm -1 are assigned to the m 3 antisymmetric vibrational mode of the CO 3 2-group, while the peaks at 1066 and 848 cm -1 are ascribed to the symmetric stretching mode m 1 and the out-of-plane bending mode m 2 , respectively [41]. It is noteworthy that the peaks at 1107 cm -1 corresponds to the Bi-S bond vibrations [42] were observed for sulfurized samples. Furthermore, this intensity of this peak at 1107 cm -1 enhanced slightly with increase of sulfurization, which implied that S atom successfully was introduced into (BiO) 2 CO 3 .…”
Section: Resultsmentioning
confidence: 84%
“…Among them, BiOI has the maximum absorption abi-lity in visible-light region due to its smallest band gap (≈ 1.8 eV) [13]. However, due to the low separation efficiency of photogenerated electrons and holes, the photocatalytic activity of BiOI is very poor [14][15][16].…”
Section: Introductionmentioning
confidence: 99%